IMPORT DEMAND AND DOMESTIC PRODUCTION OF ORANGES AND POTATOES IN INDONESIA - , Tommy Sulistyadi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Indonesia with more than 230 million people is considered an interesting market for any kind agricultural commodity including oranges and potatoes. The consumer preference has caused some change of import demand and influence domestic production for both commodities. The study uses ordinary least square with robust standard error to identify the relationship between import demand and domestic production for oranges and potatoes under same independent variables. The import relative price of oranges has opposite significant result with import demand, while, for potatoes, real income and relative price give significant contribution to import demand with different direction compared to the result for oranges, respectively. In terms of domestic production, urbanization, real income, exchange rate, and trend variables, they give important contribution to oranges domestic production while only real income gives significant impacts to potatoes domestic production. Based on these results, it is suggested that government reduces cost constraints in inputs and distribution chain, increases crops productivity, improves consumption promotion program, develops regional market and promotes food industrial absorption. In addition, the improvement of crops quality and promotion on farm management are important for enhancing national product competitiveness.